Implementación de un sistema de video vigilancia mediante cámaras ip para la seguridad en el bloque académico “a” de la Universidad Técnica de Cotopaxi extensión La Maná - Hernández Ramos, Norma Abigail (2015)
Technical University Extension Cotopaxi La Maná, in the efforts to continuously improve the safety and integrity of both its facilities and its students, teachers, workers and employees has been constantly evolution and is for thatthis research work has all the mechanisms through video surveillance outside facilities, for thiswas used some materials, including security cameras, router, NVR server and a computer that are most important and appropriate to implement a video surveillance system using IP cameras are used .